PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN - Amin, Mohammad Arridho Nur (LP2M Universitas Bina Bangsa, 2025)
The purpose of this study was to determine whether Financial Literacy and Financial Attitudes have an effect on financial management behavior partially or simultaneously on MSME actors in Suradadi District, Tegal Regency. It is hoped that this study can be a reference and benefit to improve MSME financial management. This study uses a quantitative method, the population in this study are MSME actors in Tegal Regency in Suradadi District with a total of 137 MSME actors, while the sample in this study was 102 MSME actors. Data collection techniques used are observation, interview, questionnaire and documentation methods. The analysis technique used is multiple linear analysis. The results of the study prove that there is an influence between financial literacy variables on financial management behavior, financial attitude variables do not affect financial management behavior, and financial literacy and financial attitudes have a simultaneous effect on financial management behavior on culinary MSME actors in Suradadi District, Tegal Regency.